Digital bridges to health: overcoming telemedicine barriers in rural Pakistan - Hamid Bin Tariq; Saeed, Suleman (Journal of the Pakistan Medical Association, 2025)
Dear Editor, Telemedicine has emerged as a promising solution to address healthcare imbalance in rural areas of Pakistan, where approximately 63% of the residents have limited access to medical service. The doctor-to-patient ratio in Pakistan is at 1:1300, significantly higher than WHO’s recommended ratio of 1:1000.(1) This workforce shortage highlights the need to implement telemedicine for bridging the gap by offering timely consultations, improved continuity of care and increased flexibility. However, several challenges hamper the effective incorporation of telemedicine. Pakistan’s technology sector remains critically underdeveloped. A significant portion of the population, particularly in rural areas, lacks smartphones or stable internet access.(2) This digital divide, coupled with electricity shortages, further complicates telemedicine projects, leaving many patients without vital resources during crucial times. Inadequate knowledge of technological skills makes the adoption of telemedicine much more challenging. Lack of awareness leaves many with no option but to follow the traditional system of in person consultation. Several medical facilities in Pakistan are already overwhelmed, resulting in prolonged waiting times, unjustifiably high consultation fees, and staff burnout. While telemedicine might mitigate some of these issues, establishing telemedicine platforms requires substantial financial commitment.(2) Pakistan's healthcare expenditure per capita is around USD 38, much lower than other developing nations, which is insufficient for such advancements.(3) Furthermore, most rural healthcare facilities in Pakistan still rely on paper-based medical records, and absence of robust data protection regulations raises privacy concerns, discouraging patients from using telemedicine services. Transitioning to electronic health records is vital for building trust among patients. Proper regulation involving healthcare and IT professionals is necessary to ensure the safety and sustainability of telemedicine. (4) To address these challenges and effectively integrate telemedicine into Pakistan’s healthcare system, recommendations will need to be acted upon. Firstly, the government should invest in developing internet infrastructure, by collaborating with telecom companies to make smartphones and high-speed internet connections more affordable. Secondly, general training and certifications must be given to practitioners for effective virtual care provision. (5) A regulatory framework must also be established to safeguard of patient data, privacy and security. Thirdly, conducting pilot projects in poverty-stricken areas can determine the profitability and accuracy of telemedicine, allowing implementation of necessary changes prior to a countrywide launch. By addressing these barriers, the Government can gradually facilitate the integration of telemedicine, improving access to healthcare services for disadvantaged populations.